The importance of being Alfred -- from the king of West Saxons to Nobel - Walkowiak, Justyna B. (My University, 2016)
The article appeared in a Festschrift devoted to a distinguished Polish linguist Professor Alfred F. Majewicz. It discusses the Christian name Alfred born by the Jubilarian in its various aspects: its Anglo-Saxon origins, etymology and popularity (past and present) in various European countries, with particular emphasis on Poland. It also presents some famous people, literary characters and pop culture heroes bearing this name.
Keywords: Christian names; male names; Alfred; name popularity; Anglo-Saxon names; first names; imiona celtyckie; imiona męskie